Journal Economics, business & accountancy : AUDITORS PERSONALITY IN INCREASING THE BURNOUT - Utami, Intiyas , Nahartyo, Ertambang (PPPM Perbanas, 2013)
Auditors; personality is deemed to have some effects on the burnout. This factor is consideredimportant when the increase or decrease of burnout is identified.